PERBEDAAN TINGKAT KEPATUHAN PENGOBATAN PASIEN HIPERTENSI DI WILAYAH DESA JATISARI DAN KELURAHAN PATRANG: PERBEDAAN TINGKAT KEPATUHAN PENGOBATAN PASIEN HIPERTENSI DI WILAYAH DESA JATISARI DAN KELURAHAN PATRANG - Maftuchah Legina C; Hella Meldy Tursina (Jurnal Medika Hutama, 2023)
Introduction: Adherence is the behavior of patients in undergoing treatment by following the recommendations of therapy and health given by health professionals. This study aims to determine differences in the level of adherence to treatment of hypertension patients in the Jatisari Village and Patrang Jember Villages.Methods: The research used in this research is comparative quantitative where the population in this study are patients with hypertension in the Jatisari and Patrang villages, totaling 85 respondents. The sampling technique used non-probability sampling with consecutive sampling type as many as 43 respondents from Jatisari Village and 42 respondents from Patrang Village. Collecting data in this study using the MMAS-8 questionnaire to obtain compliance data and using a questionnaire to obtain data about, gender, education level, occupation using a questionnaire sheet. The test carried out in this study was bivariate with the Mann Whitney test.Analysis and Discussion: Obtained in Jatisari village the level of compliance in Jatisari village, 22 respondents (51.2%), medium 14 respondents (32.6%), high 7 respondents (16.2%), for the results of Patrang Village the level of compliance in Patrang Village was low 10 respondents (23.8%), moderate 22 respondents (52.4%), high 10 respondents (23.8%). From the results of the Mann Whitney bivariate test, the interpretation of the significance value (ρ-value) or = 0.023 <0.05.Conclusion: there is a difference in the level of adherence to hypertension treatment in the Jatisari and Patrang villages. It is recommended that patients with hypertension take antihypertensive drugs regularly and improve a clean and healthy lifestyle and reduce stress levels.